Stardust surprise - Lindsay, Elizabeth; Currey, Anna (Usborne Publishing Ltd. London, England, 2009)
Lila and her friends are learning about stardust at Silverlake Fairy School. The fairies are not supposed to use it by themselves, but naughty Princess Bee Balm is determined to break the rules to boost her own magical powers